Molecular characterization of herbicide resistance and investigation of physiological basis of herbicide efficacy in wheat (Triticum aestivum L.) - Bynegeri, Akshitha Reddy (My University, 2026)
Wheat (Triticum aestivum L.) is a major global food and cash crop, yet its productivity is strongly constrained by weed competition and the evolution of herbicide-resistant weed populations. Post-emergence (POST) application of herbicides is the primary tool for weed management in wheat, but growers rely on a limited number of herbicide modes of action groups, and repeated use of these herbicides has selected for resistant weed biotypes and reduced the long-term effectiveness of current management programs. Hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting triketone herbicides such as mesotrione and tembotrione provide broad-spectrum weed control in corn, which is naturally tolerant through rapid, cytochrome P450 enzyme-mediated metabolism, but these herbicides are not registered for use in wheat because the crop is sensitive and suffers severe injury. Protoporphyrinogen oxidase (PPO)-inhibiting herbicides are also important tools for weed control in other crops yet can cause substantial injury to wheat. Therefore, there is a need to expand options for POST management of wheat by exploring sources of wheat tolerance to other herbicide modes of action groups, including HPPD- and PPO-inhibiting herbicides. Previously, our lab developed transgenic spring wheat lines in which either a wheat cytochrome P450 gene (CYP81Q32-like) or a wheat HPPD gene (TaHPPD) was overexpressed to target HPPD-inhibiting herbicides. Callus-derived T0 transgenic wheat lines were developed by biolistic transformation and in vitro regeneration. Part of my thesis aims to further characterize wheat lines overexpressing CYP81Q32-like or TaHPPD for tolerance to triketone HPPD-inhibiting herbicides. Similarly, previous research identified two winter wheat genotypes with elevated tolerance to PPO-inhibitors (lactofen and fomesafen), and they were characterized further in this research. The objectives of this thesis were to a) characterize the physiological and molecular basis of triketone herbicide tolerance in transgenic wheat overexpressing key metabolic and herbicide target-site genes (Chapter 2), b) determine the metabolic fate of mesotrione in CYP81Q32-like overexpressing wheat lines using radiolabeled herbicide (Chapter 3), and c) evaluate winter wheat and mutant spring wheat responses to PPO-inhibiting herbicides and identify variation in crop tolerance among winter wheat genotypes and mutant lines (Chapter 4). All experiments were conducted in controlled-environment growth chambers, greenhouses, or laboratory conditions using wild type (Bobwhite), transgenic lines, and selected winter wheat genotypes and spring wheat mutant lines. In Chapter 2, transgenic spring wheat lines overexpressing a putative metabolic gene, CYP81Q32-like (cytochrome P450), or the HPPD target-site gene, TaHPPD, were advanced to the T2 and T3 generations and evaluated for response to POST-applied mesotrione at 4-6x the labeled field rate, where x is the field-recommended rate under controlled conditions. PCR was used to confirm the presence of the transgenes, and RT-qPCR was used to quantify CYP81Q32-like and TaHPPD transcript levels. Visual injury ratings and growth measurements showed that lines with higher CYP81Q32-like or TaHPPD expression had markedly lower mesotrione injury and better recovery than wild-type plants, and crosses between CYP81Q32-like and TaHPPD lines produced F1 and F2 progenies in which individuals expressing both genes at high levels displayed the greatest tolerance, indicating that metabolic and target-site mechanisms can be combined to enhance mesotrione tolerance in wheat. In Chapter 3, the metabolic fate of mesotrione was examined in advanced CYP81Q32-like-overexpressing lines using [phenyl-U-14C]-mesotrione. Absorption and translocation studies showed no difference between transgenic and wild-type wheat, indicating that CYP81Q32-like overexpression does not alter mesotrione uptake or movement within the plant. However, high-performance liquid chromatography revealed that wild-type plants retained almost all of the parent (active form) mesotrione, whereas CYP81Q32-like lines rapidly metabolized the herbicide and produced a unique metabolite peak that was not detected in wild type, demonstrating that overexpression of CYP81Q32-like increases mesotrione metabolism in wheat and supporting P450-mediated detoxification as a key mechanism of triketone tolerance. In Chapter 4, the research was extended to other herbicide modes of action groups by evaluating wheat responses to PPO-inhibiting herbicides such as lactofen and fomesafen. Winter wheat genotypes and mutant lines were screened under controlled conditions for variation in crop injury and biomass reduction following PPO inhibitor treatment. The results showed that some wheat lines were highly sensitive to PPO inhibitors, whereas others displayed reduced injury, suggesting underlying physiological or genetic differences that may be useful for identifying or developing PPO-tolerant germplasm. The results of this thesis suggest that a) overexpression of CYP81Q32-like and TaHPPD can substantially reduce mesotrione injury in wheat; b) CYP81Q32-like enhances mesotrione metabolism without altering herbicide uptake or translocation, and c) stacking metabolic and target-site mechanisms can further improve triketone tolerance. The work also demonstrates that PPO-inhibiting herbicides can cause serious crop injury in sensitive wheat backgrounds, reinforcing the need to identify tolerant lines before these herbicides can be widely used in wheat production. Overall, these findings provide a physiological and molecular foundation for developing wheat cultivars with improved tolerance to HPPD- and PPO-inhibiting herbicides and for diversifying chemical weed-management options in wheat-based cropping systems.
Keywords: Lactofen and Fomasafen, CYP81Q-32 like, TaHPPD, Mesotrione, Herbicide resistance, Metabolic resistance , Gene expression